Dynamic Dc-Link Voltage Control of Back to Back Modular Multilevel Converter for Drive Applications - Rojas-Lobos, F; Diaz-Diaz, M; Verdugo-Naranjo, D; Lillo-Cartes, J (IEEE Computer Society, 2019)
In this work a dynamic control of the dc-link voltage in a hybrid Back-to-Back (BtB) Modular Multilevel Converter for medium-voltage drive applications is presented. The proposed control scheme relates the speed of the machine with the dc-link voltage magnitude to reduce the large circulating currents and common-mode voltage of the converter when the machine operates at low speed. Simulation results, performed in the software PLECS, validate the model of the BtB converter and the proposed control scheme, reducing circulating currents and common mode voltage in almost 70% and 60% respectively, when the machine operates at very low speed. © 2019 IEEE.